3D virtual reconstructions at the service of computer assisted archaeological measurements - Georgopoulos, Andreas; Ioannidis, Charalabos; Ioannides, Marinos (My University, 2010)
Technological advances have enabled photogrammetric and surveying methods to produce recording materials surpassing the traditional line drawings in accuracy and completeness. These methodologies may offer products not possible in the past. This paper relates the difficult experience of collecting, archiving, processing, combining, visualizing and exploiting data from a multitude of sources to make accurate geometric records of monuments, implementing the most contemporary, innovative and technologically advanced methods. Issues analysed include collecting and processing field data from a variety of sources and their respective properties, but also the production of different end products, vector and raster, with the main emphasis on complex 3D visualizations. Different approaches are assessed for their usefulness and potential accuracy. Examples covering a variety of Greek and Cypriot monuments are presented, which are acquired from the rich experience of the archaeological surveys of the Laboratory of Photogrammetry of NTUA.
Keywords: 3D visualizations